Computerized APPLICATION SYSTEM IN HOTEL FRONT OFFICE Rene Muara Enim - Balqia Siddik Z,; Ir.Aqwam Rosadi Kardian, MM (Jurnal Sistem Informasi, 2003)
The rapid development of computer lately almost covers all areas of life one of them is the usage of computers or computerized on hospitality. The development of increasingly sophisticated personal computers and the increasingly rapid process but with a smaller form than the initial discovery so the price becomes more affordable and easily obtainable. So that the third jasmine bertarap hotels can also apply computerization.